Polo-like Kinase 1-targeting Chitosan Nanoparticles Suppress the Progression of Hepatocellular Carcinoma - Wang, Dongzhi; Chang, Renan; Wang, Gang; Hu, Baoying; Qiang, Yong; Chen, Zhong (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Recent investigations have implicated that Chitosan-nucleotide nanoparticles might be useful non-viral carriers in gene therapy. Polo-like kinase 1 (PLK1) has been reported to be an important oncogene that exerted considerable therapeutic merit in hepatocellular carcinoma (HCC). Objective: We explored whether Galactosylated chitosan-graft-poly(ethylene glycol) (GCP) nanoparticlemediated delivery of PLK1 siRNA nucleotides could serve as an effective anti-cancer agent for HCC therapy. Method: GCP nanoparticles were prepared to deliver PLK1 siRNA oligos into HCC cells and tissues. Real-time fluorescence quantitative PCR (RFQ-PCR) and western blotting analyses were used to examine the efficiency of nanoparticle-mediated depletion of PLK1 in HepG2 cells. Cell proliferation and apoptotic death were also examined using flow cytometric, MTT and TUNEL assays. Xenograft mouse model was conducted to assess the impact of GCP/siRNA nanoparticles on the in vivo growth of HCC cells. Results: GCP nanoparticles bind to PLK1 siRNA efficiently. The particle size and zeta potential of GCP/siRNA nanoparticles are suitable for cellular delivery. PLK1-targeting nanoparticles inhibited cell proliferation through inducing G2/M phase arrest with a higher efficacy than a selective and potent PLK1 inhibitor BI 2536. Moreover, TUNEL assay revealed that PLK1-siRNA nanoparticles induced apparent apoptosis in HepG2 cells. In addition, PLK1-targeting nanoparticles induced significant upregulation of cellular p53, Bax and p21, whereas the level of Bcl-2 was impaired in HCC cells. Moreover, PLK1-targeting nanoparticles impaired the tumorigenicity of HepG2 cells in vivo. Conclusion: These findings indicate that PLK1-targeting nanoparticles exert considerable therapeutic merit and GCP/siRNA nanoparticles would be a valuable therapeutic carrier for HCC.
Keywords: hepatocellular carcinoma